Ontologi Kesehatan Ekosistem: Hakikat Serangan Hama dan Keberadaan Pohon Sebagai Entitas Hidup di Hutan Kota Mataram - Jannah, Husnul; Sahidu, Arifuddin; Sarjan, Muhammad (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to examine the nature of pest attacks and the status of trees as living entities within the ecosystem of the Mataram Urban Forest through an ontological perspective. A qualitative–philosophical approach with a conceptual–exploratory design was employed, integrating systematic literature analysis and field observations across ten observation points. The findings reveal damage to leaves, stems, and fruits in several tree species—including mahogany, rain tree, and acacia—which indicates weakened ecological relations between trees and their surrounding environment. Pest occurrences were not merely biological disturbances but functioned as existential markers that signal systemic ecological disharmony resulting from environmental pressures such as high daytime temperatures, low humidity, and moderate vegetation structure. The ontological modeling identified five key interrelated entities—trees, pests, the environment, visitors, and comfort—that collectively shape ecosystem health through relational balance. This study concludes that ecosystem health is driven not by the mere absence of pests but by the quality of interactions among living entities and their ecological context. The ontological approach presented here offers a foundation for more holistic and sustainable urban forest management.